(untitled) (Práxis Educativa, 2022)
In this study, it was sought to understand how teachers who work in rural schools constitute the presentification of the be-in-the-countryside to signify their existence from the rurality of their presence. The Narrative Research is used as a method, with emphasis on the biographical-narrative movement, associated with the qualitative approach and anchored in the bases of phenomenology and hermeneutics. The research devices taken as a possibility for data collection and production are configured around narrative interviews and ethnographies in the countryside. It is concluded that the rurality of presence proved to be a possibility of translating the meanings of living on the countryside and gathering conditions to review the countryside that each person produces, placing themselves as masteries of the diverse ruralities that each person living in the countryside takes to represent and signify their ways of existing in the rural and producing life and their experiences with and in the countryside. Keywords: Rurality of presence. Narrative Research. Teaching in the countryside.